The Effectiveness of Animated Video Media with Pictures on Elementary School Students' Interest in Learning and Reading Skills: A Systematic Literature Review - Mahendra, Yasinta; Fuad, Muhammad; Maulina, Dina; Suprapto, Irawan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the effectiveness of animated video media with pictures on learning interest in reading skills of elementary school students based on the results of previous research. The research method used is Systematic Literature Review (SLR). Data collection through Google Scholar. Inclusion criteria include (1) vulnerable articles in 2019-2024, (2) keywords used “animated video media with pictures”, “interest in learning”. (3) full text articles, (4) in Indonesian or English. Of the 260 documents related to animated video media with pictures, and of these 172 articles were obtained specifically discussing the context of interest in learning, only 15 articles met the inclusion criteria for the analysis stage. Data analysis includes identification and selection of articles based on inclusion criteria, data extraction, selection based on relevance, and thematic analysis of research findings. The findings show that animated video media with pictures is effective in increasing interest in learning through visual and audio presentations that are able to attract attention, create a pleasant learning atmosphere, and encourage active involvement during the learning process, especially in reading skills. In addition, the use of animation has been shown to help students understand reading content more easily through multisensory stimulation that is in line with their developmental characteristics. Based on the synthesis of findings, animated video media with pictures can be recommended as an alternative innovative and relevant learning media to support increasing interest in learning reading skills in elementary school students.